2000
DOI: 10.1088/0741-3335/42/5a/318
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the transport barriers formation at lower hybrid heating in the FT-2 tokamak experiments

Abstract: The possibility of controlling the transport processes in the tokamak plasma in the lower hybrid heating (LHH) experiment has been demonstrated. We illustrate experimentally the observed transport barrier formation initialized by the LHH for different plasma experiment scenarios. First, it was found during LHH. The next method to trigger improved confinement is a combination of fast current ramp-up with LHH. The mechanisms of internal barrier formation have been put forward to explain the observed regime of im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Most experiments have achieved internal transport barriers (ITBs) by adding auxiliary heating 2,3,4,5,6 beyond some threshold value resulting in distinct changes in the heat, momentum, or particle transport from one region of the plasma to another. It has also been demonstrated that reversal of magnetic shear by use of current modification by lower hybrid current drive 7 or electron cyclotron current drive 8 encourages ITB development. These are thought to occur when the effects of pressure profile gradient driven instabilities are reduced by the introduction of rotational shear into the unstable region or by providing a region of reversed magnetic shear 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Most experiments have achieved internal transport barriers (ITBs) by adding auxiliary heating 2,3,4,5,6 beyond some threshold value resulting in distinct changes in the heat, momentum, or particle transport from one region of the plasma to another. It has also been demonstrated that reversal of magnetic shear by use of current modification by lower hybrid current drive 7 or electron cyclotron current drive 8 encourages ITB development. These are thought to occur when the effects of pressure profile gradient driven instabilities are reduced by the introduction of rotational shear into the unstable region or by providing a region of reversed magnetic shear 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the increase of T e (r = 2 cm) from 400 eV up to 650 eV during LHH is followed by a further heating up to 700 eV in the post-heating stage. The persisting high values of T e (r) after the RF pulse indicate that electron heating is not only due to RF power absorption but also due to ICC (see figure 1 in [2], where the first scenario is described in detail. )…”
Section: Methodsmentioning
confidence: 99%
“…The LCFS is the last of the closed flux surfaces to touch the poloidal limiter at the same point. The L-H transition has been observed in experiments with additional plasma heating by lower hybrid (LH) waves [1,2]. The working gas is hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…Other techniques use radio frequency waves to alter the internal magnetic configuration of the plasma to obtain magnetic shear stabilization of microturbulence. These include lower hybrid current drive [18,19], electron cyclotron heating [20] and ion Bernstein wave injection [21]. A comprehensive review of the internal transport barrier (ITB) experiments and analysis can be found in papers by Wolf [22] and Connor [23].…”
Section: Introductionmentioning
confidence: 99%